2021
DOI: 10.3389/fped.2020.582375
|View full text |Cite
|
Sign up to set email alerts
|

Neurodevelopment Outcome of Neonates Treated With Intraventricular Colistin for Ventriculitis Caused by Multiple Drug-Resistant Pathogens—A Case Series

Abstract: Background: Multiple-drug-resistant Gram-negative bacteria (MDR-GNB)-associated neonatal ventriculitis is a life-threatening complication that needs timely diagnosis and effective treatment with broad-spectrum antimicrobials in critical-care settings. Inadequate penetration of antibiotics through the blood–brain barrier also demands an intraventricular (IVT) route of administration. This study reports mortality and neurodevelopmental sequelae of neonates till 18 months of age, who received IVT-colistin for tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(26 citation statements)
references
References 56 publications
1
22
0
Order By: Relevance
“…Our patient had developed multiple brain abscesses which were managed successfully via thorough medical and neurosurgical treatments. Multi Drug Resistance -Gram Negative bacterial neonatal infections including intracranial infections is a great concern of increased prevalence in some middle and low-income countries which leads to greater morbidity and mortality rates [8]. Thus, despite negative blood and CSF culture results which might be due to technical issues, our patient was started on Intravenous Colistin in combination with Rifampin and Ciprofloxacin.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Our patient had developed multiple brain abscesses which were managed successfully via thorough medical and neurosurgical treatments. Multi Drug Resistance -Gram Negative bacterial neonatal infections including intracranial infections is a great concern of increased prevalence in some middle and low-income countries which leads to greater morbidity and mortality rates [8]. Thus, despite negative blood and CSF culture results which might be due to technical issues, our patient was started on Intravenous Colistin in combination with Rifampin and Ciprofloxacin.…”
Section: Discussionmentioning
confidence: 97%
“…Due to limited penetration of Colistin into the blood brain barrier, simultaneous administration of Colistin via an EVD may enhance survival and improve neurodevelopmental outcomes [8,11]. However, there is limited data on using intraventricular Colistin in neonatal intracranial infections.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study addressed the use of colistin in neonates, which is one of the largest series of its kind, and the authors found that six out of seven patients who received IT/IVT colistin survived, where five of them received it in combination with IV colistin, and the one that died received only IT/IVY colistin [ 29 ]. The study went on further to report the neurodevelopmental outcome.…”
Section: Discussionmentioning
confidence: 99%
“…The study went on further to report the neurodevelopmental outcome. The authors reported three patients who had a seizure disorder on follow-up, and the only patient with moderate disability had both hearing and visual impairments [ 29 ].…”
Section: Discussionmentioning
confidence: 99%